Computational thinking and tinkering : exploration study of primary school students in robotic and graphical programming - Felicia Anna, Sha'rif Sabariah, Wong Wk, Mariappan Muralindran, (Universiti Pendidikan Sultan Idris, 2017)
Computational thinking and tinkering : exploration study of primary school students in robotic and graphical programming by Felicia Anna, Sha'rif Sabariah, Wong Wk, Mariappan Muralindran,